Integrating chemistry and immunology in allergic contact dermatitis: more questions than answers? - Lonsdorf, Anke Susanne; Enk, Alexander (The journal of investigative dermatology, 2011)
In this issue, Simonsson and colleagues shed light on the chemical mechanisms determining hapten formation in the skin, which precede the elicitation of an antigen-specific immune response in allergic contact dermatitis. Combining fluorescence microscopy, proteomics, and mass spectrometry, the investigators identified keratins K5 and K14, particularly cysteine 54 of K5, in the human basal epidermal layer as the major molecular targets of caged thiol-reactive fluorescent haptens (i.e., bromobimanes). Anti-keratin antibody responses in mice exposed to bromobimanes suggest the generation of immunogenic epitopes by cysteine-reactive haptens. Although many issues await further investigation, Simonsson and co-workers’ observations advance our understanding of the molecular basis of hapten-protein complex formation in skin.
Elektronische Reproduktion der Druck-Ausga
Available online 8 December 2015
Gesehen am 10.10.2022